Peningkatan Kualitas Pembelajaran Bahasa: Implementasi Media Ajar Digital di Sekolah Terbuka Madani, Kota Depok - Indrayani, Septina; Sukaesih, Ina; Edel, Eky Erlanda; Humolungo, Farizka; Safitry, Tantri Sari Safitry; Kurniawati , Dewi (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2024)
Technology is advancing at a quick pace, which means that we need experienced teachers who can create engaging, digital-based lesson plans in addition to being skilled at teaching to students' needs. In order to improve the proficiency of the teachers at the Madani Middle and High School integrated schools in Depok, a community program based on the Science and Technology Implementation Service was implemented. The outcomes of this community service, which combined theory and practice, demonstrated that training in creating instructional media using the Prezi application, particularly for language learning, was able to enhance teachers' proficiency in using technology-based teaching tools. Keywords - digital competence, teaching media, Prezi   Abstrak Seiring dengan perkembangan teknologi yang pesat, dibutuhkan guru berpengalaman yang dapat membuat rencana pembelajaran berbasis digital yang menarik serta terampil dalam melakukan pembelajaran yang sesuai kebutuhan siswa. Dalam rangka meningkatkan kemahiran para pengajar di sekolah terpadu SMP dan SMA Madani di Depok, dilaksanakan program Pengabdian Penerapan Iptek berbasis Masyarakat (PPIBM). Hasil dari pengabdian kepada masyarakat yang menggabungkan teori dan praktik ini menunjukkan bahwa pelatihan pembuatan media pembelajaran dengan menggunakan aplikasi Prezi khususnya untuk pembelajaran bahasa mampu meningkatkan kemahiran guru dalam menggunakan perangkat pengajaran berbasis teknologi. Kata Kunci - kemahiran digital, media ajar, Prezi